2021
DOI: 10.1002/erv.2834
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of network analysis studies in eating disorders: Is time to broaden the core psychopathology to non specific symptoms

Abstract: Objective Network theory considers mental disorders as the product of symptom interaction. A growing number of studies employing this methodology has been conducted in eating disorders (EDs). We aimed to review those studies to provide evidence and limitations for a novel conceptualisation of EDs. Methods According to PRISMA guidelines and PICOS criteria, studies eligible for inclusion were those employing network analysis in people with a clinically defined diagnosis of ED. Twenty‐five studies were included a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
80
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(106 citation statements)
references
References 61 publications
22
80
4
Order By: Relevance
“…Targeting these dysfunctional thoughts could help reducing ED-specific core symptoms and ED-related psychopathology and would be beneficial for cognitive change. In line with the promising method to reconceptualize ED that is network analysis [10], our results support to broaden the core psychopathology to non-ED-specific cognitive symptoms. Including additional psychological cognitive features in the assessment of EDs might yield incremental data to better evaluate and treat the complex interplay characterizing ED psychopathology.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Targeting these dysfunctional thoughts could help reducing ED-specific core symptoms and ED-related psychopathology and would be beneficial for cognitive change. In line with the promising method to reconceptualize ED that is network analysis [10], our results support to broaden the core psychopathology to non-ED-specific cognitive symptoms. Including additional psychological cognitive features in the assessment of EDs might yield incremental data to better evaluate and treat the complex interplay characterizing ED psychopathology.…”
Section: Discussionsupporting
confidence: 83%
“…The irrational belief of negative global evaluations was found instead to be the most significant predictor of non-specific ED general psychological maladjustment, which includes aspects pertaining to perfectionism, self-esteem, inefficacy, and interpersonal difficulties. Feelings of inefficacy in particular have been hypothesized to play a core role in clinical models of Eds, and they have been empirically supported, using network analysis procedures, to reach centrality among nodes of the network of symptoms of ED patients [10,48]. ED patients commonly present low self-esteem, low self-efficacy, and beliefs of incompetence [31,[49][50][51][52] linked with ED symptomatology even when considering confounding depressive symptoms [53].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most previous studies using the network approach in psychopathology have assessed the patterns between specific symptoms of eating disorders via cross-sectional study designs, as revealed by a recent review (Monteleone & Cascino, 2021). In particular, two studies evaluated longitudinal networks of eating disorder symptoms, the first assessing participants at risk of eating disorder onset (Levinson, Vanzhula, Smith, & Stice, 2020), and the second evaluating participants with self-reported anorexia nervosa symptoms; the latter was designed to examine the trajectory of symptom change associated with the use of a digital guided self-help intervention to augment treatment as usual (Monteleone et al, 2020).…”
Section: Introductionmentioning
confidence: 99%